2020
DOI: 10.9734/ejnfs/2020/v12i1130329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sesame Seed Oil (Black /White) as a Natural Antioxidant on the Oxidative and Frying Stability of Linseed Oil

Abstract: Aims: In today's scenario, the oil industry is striving for natural and newly synthesized bioactive compounds due to their distinct nutritional, safety and health benefits over chemically synthesized antioxidants. Sesame seeds are conventionally perceived as the wealthy source of bioactive lignans. Both water-soluble and oil-soluble lignans in sesame oil (SO) and sesame cake have been proclaimed to have therapeutic benefits on humans. On the contrary, linseed oil (LO) due to its high concentration of alpha-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The works [8,[18][19][20][21][22][23] present data on various methods of oxidative stabilization of linseed oil using special storage films that absorb oxygen, as well as various types of antioxidants. Thus, the authors [22] showed the effectiveness of ascorbic acid esters.…”
Section: Discussion Of the Results Of Determining The Rational Concen...mentioning
confidence: 99%
See 2 more Smart Citations
“…The works [8,[18][19][20][21][22][23] present data on various methods of oxidative stabilization of linseed oil using special storage films that absorb oxygen, as well as various types of antioxidants. Thus, the authors [22] showed the effectiveness of ascorbic acid esters.…”
Section: Discussion Of the Results Of Determining The Rational Concen...mentioning
confidence: 99%
“…Thus, the authors [22] showed the effectiveness of ascorbic acid esters. According to [23], oxidative stabilization of linseed oil using tert-butylhydroquinone and butylhydroxytoluene with the addition of garlic extract is appropriate. The main method of increasing the oxidative stability of linseed oil is the addition of various types of antioxidants, which was used in this work.…”
Section: Discussion Of the Results Of Determining The Rational Concen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by El-Roby, Hammad, and Galal [ 14 ] found that ethanolic extract of sesame seed coat has an antioxidant activity similar to tocopherol. Prakash et al [ 22 ] demonstrated that a black sesame coat had a higher antioxidant activity compared to a white sesame coat.…”
Section: Introductionmentioning
confidence: 99%